2016
DOI: 10.1177/2374289516633476
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Educate Family Physicians to Change Test Ordering

Abstract: The purpose is to systematically review randomised controlled trials (RCTs) to change family physicians’ laboratory test-ordering. We searched 15 electronic databases (no language/date limitations). We identified 29 RCTs (4,111 physicians, 175,563 patients). Six studies specifically focused on reducing unnecessary tests, 23 on increasing screening tests. Using Cochrane methodology 48.5% of studies were low risk-of-bias for randomisation, 7% concealment of randomisation, 17% blinding of participants/personnel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…However, the size of the reduction in test volume seen in this study was far greater than that generally reported. 4,5 We anticipated that there may have been more questions or concerns given that a recent survey of Alberta primary care physicians showed that specialized test requisitions for certain tests were felt to be acceptable to only 45% of survey respondents. 17 In the current era of unsustainable increases in laboratory test volumes in Canada, 18,19 the managed exit of low-value tests is needed to ensure resources are available for medically necessary tests.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the size of the reduction in test volume seen in this study was far greater than that generally reported. 4,5 We anticipated that there may have been more questions or concerns given that a recent survey of Alberta primary care physicians showed that specialized test requisitions for certain tests were felt to be acceptable to only 45% of survey respondents. 17 In the current era of unsustainable increases in laboratory test volumes in Canada, 18,19 the managed exit of low-value tests is needed to ensure resources are available for medically necessary tests.…”
Section: Discussionmentioning
confidence: 99%
“…This group identified 5 priority recommendations for implementation in Alberta, one of which was the recommendation against population-based screening for serum total 25-hydroxyvitamin D (vitamin D) deficiency. This recommendation was jointly put forward by The Canadian Association of Pathologists 5 Implementation of an intervention to reduce populationbased screening for vitamin D deficiency: a cross-sectional study Vitamin D screening has been particularly problematic for the health system in Alberta because there has been a massive increase in test volumes over the past 10 years, 9 with evidence that testing has been preferentially directed toward low-risk patients. 10 We describe the implementation of an intervention in Alberta in support of the Choosing Wisely Canada recommendation against population screening for vitamin D deficiency.…”
Section: Hoosing Wiselymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a recent survey of family physicians showed that nearly all (98 percent) were accepting of educational utilization management interventions (Thommasen et al 2016). However, a high-quality randomized controlled trial of such education showed no effect on utilization (Thomas et al 2016).…”
Section: The Trade-off Between Effectiveness and Acceptabilitymentioning
confidence: 99%